Analysis of room rates setting in hotel daily operations - Izza Ulumuddin Ahmad Asshofi; Mutiara Amelia Putri; Rio Dwi Saputra; Ani Wijayanti (Journal of Gastro Tourism, 2023)
Hotels have a considerable influence in increasing regional tourism and the economy. The hotel itself means a service or service business operated and managed commercially and provided for everyone to receive services, such as rooms, accommodations, food and beverages, and other service facilities. In the tourism industry, especially in the hotel business, there is a term for room sales that has an important role as one of the elements of calculating income in hotels. The purpose of writing articles is to find out the problems that occur in setting room rates, the factors that affect setting room rates, the type of room rates, the purpose of setting room rates, and the method of determining the base price and sale price. The benefit of writing articles is to develop knowledge, especially about room rates and hospitality; to increase insight, knowledge, and experience in writing articles; to later be useful for education, especially for the hospitality industry. The method used in this writing is a qualitative method that produces information in the form of records or data, is descriptive, and tends to use analysis. Room pricing plays a major role in highly competitive businesses such as hotels because hotel room sales are the spearhead of a hotel business. Apart from the hotel having to maintain its profitability, the hotel also has to provide guests with balanced feedback according to the price paid by the guest. However, if the price setting of a hotel room is not driven by good planning and strategy, the business may fail.